2021
DOI: 10.1371/journal.pone.0249275
|View full text |Cite
|
Sign up to set email alerts
|

Dependence in instrumental activities of daily living and its implications for older adults’ oral health

Abstract: We aimed to assess the association between dependence in instrumental activities of daily living (IADL) and oral health in older adults. We conducted a cross-sectional study of 280 people aged ≥60 years served at public primary health care centers in Northeastern Brazil. Sociodemographic, oral discomfort and general health data were collected. The Lawton and Brody scale were used to assess IADL. This research adheres to the STROBE checklist. Most participants were married (n = 139; 49.6%), women (n = 182; 65.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 30 publications
2
5
0
1
Order By: Relevance
“…The Lawton scale of IADL has not been deeply investigated in the oral health; however, previous studies reported a relationship. 35 ) Similarly, few studies have investigated the relationship of the Barthel scale with oral health; among these studies, some results are consistent with the findings of the present study, in which a lower Barthel index score was generally related to poorer oral health conditions, in this case, edentulism. 36 ) This analysis revealed an OR very close to statistical significance for both the Barthel and Lawton scales in the final model and a significant relationship when they acted as independent determinants that were preserved for the Lawton scale after adjusting for sociodemographic variables.…”
Section: Discussionsupporting
confidence: 91%
“…The Lawton scale of IADL has not been deeply investigated in the oral health; however, previous studies reported a relationship. 35 ) Similarly, few studies have investigated the relationship of the Barthel scale with oral health; among these studies, some results are consistent with the findings of the present study, in which a lower Barthel index score was generally related to poorer oral health conditions, in this case, edentulism. 36 ) This analysis revealed an OR very close to statistical significance for both the Barthel and Lawton scales in the final model and a significant relationship when they acted as independent determinants that were preserved for the Lawton scale after adjusting for sociodemographic variables.…”
Section: Discussionsupporting
confidence: 91%
“…due to decreased grip strength may have a direct effect on oral health maintenance (Saintrain et al, 2021), as we have found in the current study. Given the increase in IADL disability among older adults with CF, future studies assessing the relationship between IADL disability and oral health status are needed to confirm the current results.…”
Section: Ta B L E 3 (Continued)supporting
confidence: 70%
“…Takata et al [36] conducted a study on older adults aged ≥ 80 years and found that functional dependency was 3.3-fold higher in individuals who could chew from five to nine types of food than in those who could chew 15 types of food, indicating the impact of mastication on ADL, although no significant association was shown between ADL and the number of healthy natural teeth. Nevertheless, based on the reported association between oral health status and functional dependency during daily activities in older adults, the association between the number of natural teeth, as a key oral health indicator, and the performance of daily activities may be inferred [37]. In addition, the generally reduced functional state may be attributed to the restriction of ADL, which follows the restriction of IADL.…”
Section: Discussionmentioning
confidence: 99%